A primary leiomyosarcoma of bone containing pseudoepithelial plexiform elements. - Rigopoulou, A; Vlychou, M; Ostlere, S; Gibbons, C; Athanasou, N (2007)
A rare but distinctive variant of smooth muscle tumours that occurs almost exclusively in the uterus is characterised by the presence of plexiform tumourlets, which are composed of clumps and cords of tumour cells that form a discrete pseudoepithelial component. We report on a case of a primary leiomyosarcoma of the proximal humerus, which, in addition to characteristic histological and immunophenotypic features of leiomyosarcoma, contained plexiform tumourlets. Tumour cells in the plexiform component focally expressed muscle/smooth muscle actin, calponin and cytokeratin. Spindle-shaped and epithelioid smooth muscle tumour cells also expressed the above antigens. This is the first report of a plexiform smooth muscle tumour arising in bone. This case is remarkable, not only for being only the second reported case of a malignant plexiform smooth muscle tumour, but also for being one of very few examples of this type of tumour arising outside the uterus; it also is unique in having arisen in a male patient. This variant of primary leiomyosarcoma needs to be distinguished from other bone tumours containing epithelial elements, notably metastatic carcinoma.